If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + 5 = 6x + b Reorder the terms: 5 + ax = 6x + b Reorder the terms: 5 + ax = b + 6x Solving 5 + ax = b + 6x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + ax = b + -5 + 6x Combine like terms: 5 + -5 = 0 0 + ax = b + -5 + 6x ax = b + -5 + 6x Reorder the terms: ax = -5 + b + 6x Divide each side by 'x'. a = -5x-1 + bx-1 + 6 Simplifying a = -5x-1 + bx-1 + 6 Reorder the terms: a = 6 + bx-1 + -5x-1
| A=24-(10-(20-a)) | | A=24-(10-(20-a)) | | 5(2x-3)=-105 | | 4y^2-y^2=10 | | 4y^2+y^2=10 | | y=(64)4x | | 3x-9=-15+2x | | B=10-(20-(24-b)) | | 12-21x+2x-6=-32 | | y=3x(48) | | (24-b)+(20-(24-b))=x-b | | x=2.5+1.5y | | -2x+y=-7 | | 31n=2(1.55n) | | -1/3x-3y=4/6x-1/3 | | (24-b)+b+(20-(24-b))= | | 50x(x^2-100)=0 | | 3p+15=36 | | 9x+1=36 | | 5n-8=-18 | | y=3(x)8+2(x)-9 | | 18c=90 | | y=4(x)7 | | x+5.7=8.3 | | g-10=-3 | | 23=34 | | y+7=24 | | 8(x-6)-4(x-3)+7x= | | 8u-16=0 | | -18=6w-15 | | 3x-5=10x-69 | | 1+4=95 |